Response art in art therapy practice and research with a focus on reflect piece imagery - Nash, Gary (International journal of art therapy, 2020)
This 'practice innovation' paper provides an overview of the development of 'response art' which is growing as an integral part of routine clinical practice in art therapy. I provide a literature review of the use of art therapist generated images made before, during and following clinical work. There is a particular focus on post-therapy 'reflect piece' imagery which is the subject of the research described in this paper. The purpose of the research is to examine practitioners experience when using art immediately following a session, and how making art in this context, may facilitate the discharge and release of powerful or complex affects and part-processed feelings aroused during their clinical work. Secondly, how developing the themes, gestures and visual motifs systematically between sessions may deepen empathy and attunement, and thirdly, how both forms of visual expression may contribute to the supervisory process. Plain-language summary Response art refers to the visual, creative, art-based responses made by art therapists as part of clinical practice. The generic term is 'clinical art-making' and refers to art made in response to any client-related experience, work-based dynamic material or experiences deriving from the clinical context. The term 'reflect piece imagery' is used to describe the artworks therapists make immediately following an art therapy session and is the focus of this paper. The potency and clinical usefulness of this form of response art has led to an art-based research project which I have been leading over the past two years. The second part of this paper presents examples from the research and draws together the findings from this and previous research to form an evidence-base from which practice methods and further research in this area can be developed. The literature review traces the emergence of the use of clinical art-making in art therapy practice in North America and Britain and refers to the definition, contexts and application of therapist generated artworks. The current research design described is art-based and demonstrates the use of visual research methods (McNiff, 1998 , 2013 , 2018 ) which may also be of interest to the reader as well as contributing to the practitioner-researcher paradigm.